Perception of Stakeholders towards the Shine Dental Clinic - Mainali, Sneedha (Journal of Chitwan Medical College, 2019)
Background: For the betterment of an organisation, stakeholder’s perception plays a vital role by helping to alter the environment of the workplace as well as the overall operation and management of the organisation. This study aims to explore the stakeholders’ perceptions about services and management from every aspect by studying the positive and negative remarks given by them. Methods: A descriptive cross-sectional research design was used among 68 respondents which included- patients, parents, institutional clients and employees. Results: It was found that the stakeholders of the Shine dental clinic, both the staff and clients/customers were satisfied with the by the clinic. Customers mainly build their perception to be positive or negative in terms of the factors such as the clinic’s environment, effective service delivery, maintenance of the clinic, the treatment and communication of the health workers and timely delivery of the service. Meanwhile, the staff determined the perception of the clinic in terms of salary and benefits, friendliness of top management, scope of learning and self-development, and so on. Conclusions: The stakeholders of the clinic perceived the clinic as a promising clinic and were satisfied with all the services and facilities provided to them. More people are becoming aware about the clinic with time, but it is needed for the clinic to be more visible in the social media for additional brand awareness.